Monitoring populations and threats to range‐restricted freshwater fishes: A case study of the Stocky Galaxias (Galaxias tantangara). (29th August 2022) - Lavery, Tyrone H.; Lindenmayer, David B.; Allan, Hugh; Southwell, Darren; Woinarski, John C. Z.; Lintermans, Mark
Summary: Monitoring is critical for conservation, to track the status of threatened species, assess the relative impacts of threats, inform management responses and prioritise them according to their efficacy. Globally, freshwater fish are impacted by a range of threats including deterioration in water quality, climate change, habitat loss and degradation, introduced predators and herbivores, and wildfire. Monitoring of freshwater fish can be challenging because aquatic conditions can make detecting and identifying population trends difficult for many species. Galaxiidae is the most speciose family of Gondwanan‐distributed freshwater fishes, and over 75% of species assessed by the IUCN Red List have been classified as threatened. Many Australian galaxiids are highly imperilled and monitoring effort and adequacy is low. We prepared a detailed monitoring plan for the Stocky Galaxias ( Galaxias tantangara ) that is representative of the conservation status and level of threat facing many congeneric and other similar species. Our protocol provides details of species biology, pertinent threats, and management options with sampling methods to gather these data, and options to link with management actions for maximum benefit. Improved monitoring linked with threat management should improve the conservation status of Stocky Galaxias. By providing this example, we have sought to improve monitoring for range‐restricted freshwater fishes more generally.